Fertility of buffalo semen frozen in programmable freezer - BHOSREKAR, M R; PUROHIT, J R; GOKHALE, S B; MANGURKAR, B R (The Indian Journal of Animal Sciences, 2013)
Buffalo semen, frozen by using conventional method and programmable freezer, was utilized for artificalÂ Insemination in buffaloes owned by farmers in the operational area of HAlF in 5 states, There were highly significant differences at 5% level. The semen frozen by programmable freezer showed significantly higher fertility in buffaloes as compared to conventional method, Amongst season, winter showed significantly better conception rate with frozen semen as compared to other seasons.